Hubungan antara Lingkungan Kerja Fisik dan Nonfisik dengan Kinerja Aparatur Sipil Negara - Ernawati Ernawati; Ready Gozal Isnaini; Yudhistira Ramadhany; Ardiansyah Ardiansyah; Billy Leo Richardo Kasun; Sarman Sarman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
Employee performance among Civil Servants (ASN) is largely shaped by the surrounding work environment, especially within the Personnel and Human Resource Development Agency (BKPSDM) of Paser Regency. This environment encompasses two primary elements: the physical aspect, referring to office infrastructure, facilities, and physical working conditions, and the non-physical aspect, which involves social interactions, organizational values, communication systems, and leadership support. Creating a favorable workplace atmosphere is fundamental to fostering higher productivity, stronger motivation, and improved service quality. The present research investigates how both physical and non-physical work settings affect the performance of ASN employees at BKPSDM Paser. Adopting a quantitative approach through a survey design, data were obtained using questionnaires administered to staff members. The instruments were evaluated for both validity and reliability, and multiple regression analysis was employed to identify the extent of influence from each work environment dimension on performance outcomes. The results indicate that physical and non-physical work conditions each exert a significant and positive impact on employee performance. Proper facilities and well-maintained workspaces help increase focus and efficiency, while supportive non-physical conditions—such as healthy interpersonal relationships, open communication, and a constructive organizational atmosphere—promote enthusiasm and dedication. Hence, ongoing improvements in both physical infrastructure and organizational culture are necessary for BKPSDM Paser to strengthen employee performance and elevate the quality of its public services.